Pengembangan Media Pembelajaran Video Animasi untuk Meningkatkan Minat Belajar Siswa - Suryadi, Suryadi (Attractive : Innovative Education Journal, 2024)
This research was motivated by the lack of student interest and use of video learning media, especially in grade 2 thematic learning at SDN 01 Taman Asri. The objectives of this research are: (1) Developing animated video-based media in the learning process, (2) Knowing the feasibility of animated videos in application during the learning process, whether they are able to increase students' interest in learning or not. This research uses R&D (Research and Development) research using the ADDIE development model. The product developed is Animation Video media. The subjects in this research were 2nd grade students at SDN 01 Taman Asri with a total of 13 students. The techniques and instruments used are interviews, observation, questionnaires and documentation. To measure the increase in interest using the before after technique. The results of the research show that Animation Video media is suitable for use as a learning medium with material expert validation of 100% with very feasible criteria, media 1 expert validation of 82% with valid criteria, and media 2 expert validation of 98% with very valid criteria. Animation Video Media can increase students' interest in learning, this can be seen from the results of the student interest questionnaire where in the small group the interest results before were 61% and after were 87% so that the increase in interest in learning in the small group was 26%, while in the large group the interest results before was 62.25% and after 88.25%, resulting in an increase in interest in learning in large groups by 26%. From these results it can be concluded that Animation Video media can increase the interest in learning of class 2 students at SDN 01 Taman Asri. Keywords: Animation Media, Development Animated Video, Learning Media